Eggs Fertility, and Hatchability of Kampong Hens Inseminated Using Brahma, Cochin, and Bangkok Roosters Semen - Asnawi, Asnawi; Maskur, Maskur; Dradjat, Adji Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The objectives of this research were to evaluate Brahma, Cochin, Bangkok roosters spermatozoa quality and compare fertility and hatch-ability following insemination into Kampong hens. The semen quality was evaluated using a completely random design of three strains of the rooster with 5 replications. The results showed that spermatozoa concentrations of Brahma, Cochin, and Bangkok rooster were 1252.0± 7.92x106, 1140.0± 5.83x106, and 1304.0± 12.28x106 respectively (p >0.05). The percentage of motility of Brahma, Cochin, and Bangkok spermatozoa was 72 ± 2.74 %, 74 ± 2.24 %, and 73 ± 2.74 % respectively (p>0.05). The percentage viability of spermatozoa of Brahma, Cochin, and Bangkok were 99.2 ± 1.30 %, 99.4 ± 0.55 % dan 99.2 ± 1.10 % respectively (p>0.05). The percentage normality of Brahma, Cochin, and Bangkok spermatozoa were 94.6 ± 2.30 %, 94.4 ± 2.70 % dan 97.4 ± 2.07 % respectively (p >0.05). Fertility of eggs inseminated using Brahma, Cochin, and Bangkok, spermatozoa to Kampong hens were, 36.21 ± 17.52%, 34.29 ± 14.50%, and 73.27 ± 9.90% respectively and they were significantly different (p <0.05). The hatchability of eggs inseminated using Brahma, Cochin, and Bangkok spermatozoa were 59.40 ± 34.80%, 87.26 ± 8.81%, and 82.63 ± 5.34% respectively and they were significantly different (p<0.05). It can be concluded that Brahma, Cochin, and Bangkok roosters have good quality semen, which can be used inseminate into Kampong hens.